ANALISIS PESAN MORAL PADA NOVEL BUMI KARYA TERE LIYE - Irmawati, Irmawati; Kemal, Isthifa (Jurnal Bahastra, 2023)
This study raises the topic of "Analysis of Moral Messages in Tere Liye's Bumi Novel". The purpose of this research is to describe the moral message contained in the novel Bumi by Tere Liye. The research method plays an important role in a research. This method is a method that is carried out by collecting data, describing the data, and then analyzing the data. The type of data taken from this study is qualitative. The data described from this study is the novel Bumi by Tere Liye which contains a moral message.The moral values contained in the novel Bumi by Tere Liye are the moral values of human relations with oneself, the moral values of human relations with other human beings, the moral values of human relations with God and the moral values of human relations with the natural surroundings. The manifestations of the moral values of human relations with oneself in the Bumi novel are Honesty, Curiosity, Emotional, Obedience, Assertiveness, Sacrifice, Hope, Suffering, Courage. The moral values of human relations with other human beings are loyal friends, affection, help, cooperation, harmony, attention, apologies. The form of moral values contained in the Bumi novel is praising the beauty of nature and natural sustainability. Forms of moral values that include surrender and gratitude. This study raises the topic of "Analysis of Moral Messages in Tere Liye's Bumi Novel". The purpose of this research is to describe the moral message contained in the novel Bumi by Tere Liye. The research method plays an important role in a research. This method is a method that is carried out by collecting data, describing the data, and then analyzing the data. The type of data taken from this study is qualitative. The data described from this study is the novel Bumi by Tere Liye which contains a moral message.The moral values contained in the novel Bumi by Tere Liye are the moral values of human relations with oneself, the moral values of human relations with other human beings, the moral values of human relations with God and the moral values of human relations with the natural surroundings. The manifestations of the moral values of human relations with oneself in the Bumi novel are Honesty, Curiosity, Emotional, Obedience, Assertiveness, Sacrifice, Hope, Suffering, Courage. The moral values of human relations with other human beings are loyal friends, affection, help, cooperation, harmony, attention, apologies. The form of moral values contained in the Bumi novel is praising the beauty of nature and natural sustainability. Forms of moral values that include surrender and gratitude.